PARENTS’ INVOLVEMENT IN CHILDREN'S LEARNING ACTIVITIES DURING THE COVID-19 PANDEMIC - Ria Novianti; Enda Puspitasari; Ilga Maria (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Riau, 2021)
This study utilized a survey method with a quantitative descriptive approach. This study aimed to determine the parents’ involvement in early childhood learning activities during the Covid-19 pandemic. Early childhood needs assistance during the learning process from home; therefore, the role of parents is very crucial since it gives a long-term impact on children's development. Changes in the atmosphere and climate of learning activities from the classroom to the home centainly bring new challenges. Respondents in this research were 102 parents with 4-6 years old-children in Pekanbaru. The samples were selected by using random sampling technique. The data analysis was presented in table. Overall, the results of the study on parents’ involvement which consisted of three indicators (parents' motivation, parents' perceptions of other people's invitations to be involved in children's education, and parents’ feeling) was generally high. This indicated that parents possessed good motivation to assist children in learning by understanding their important role and having confidence in accompanying childrens’ learning activities.